The EFFECT OF COMPANY SIZE, PROFITABILITY, LEVERAGE, SALES GROWTH ON FIRM VALUE IN FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Patimah, Siti; Mustika Sari, Dina; Fatmawati, Susan; Haripin, Haripin; Agnes Kurnia Tjahjono, Gabriella (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2025)
This study aims to analyze the effect of company size, profitability, leverage, and sales growth on the value of food and beverage companies listed on the Indonesia Stock Exchange. This study uses quantitative methods with multiple linear regression analysis using SPSS version 27. This study involved 84 companies as a population, with 15 companies selected as samples through purposive sampling method. The results in this study indicate that (1) Company size partially has a positive and significant effect on PBV (2) ROA partially has no positive and insignificant effect on PBV, (3) DAR partially has a negative and significant effect on PBV, (4) Sales Growth partially has a negative and significant effect on PBV, (5) Simultaneously, company size, ROA, DAR, and sales growth have an influence on PBV.